A fusidic acid-resistant (PVL+) clone is associated with the increase in methicillin-resistant Staphylococcus aureus in New Caledonia. (September 2022) - Bourles, Alexandre; Tristan, Anne; Vandenesch, François; Bes, Michèle; Laurent, Frédéric; Ranc, Anne-Gaëlle; Kainiu, Malia; Gourinat, Ann-Claire; Biron, Antoine; Cazarola, Cécile; Goarant, Cyrille; Colot, Julien
Highlights: High prevalence of fusidic acid resistance in methicillin-resistant S. aureus Dominance of community-acquired MRSA harbouring PVL toxin Low diversity with the dominance of a particular clone: CC6-MRSA-[IV+ fus ] (PVL+) Frequent fusidic acid resistance associated with high prevalence of fusC gene Recommendation to stop the topical use of fusidic acid Abstract: Objectives: Since 2014, Staphylococcus aureus methicillin resistance has been rapidly increasing in New Caledonia and is associated with potential serious clinical repercussions. In the present study, we investigated the epidemiology of methicillin-resistant S. aureus (MRSA) in New Caledonia and the possible emergence of a particular clonal strain. Methods: An overview of the distribution of MRSA in New Caledonia in 2019 is presented. We collected and analysed 171 clinical MRSA isolates from New Caledonia medical laboratories during August and September 2019. Among this collection, 49 representative isolates were analyzed by the French National Reference Center for Staphylococci using the StaphyType DNA microarray, allowing genetic characterization of the isolates. Results: Among the 1144 S. aureus isolated over the year 2019, 442 isolates (39%) were resistant to methicillin, and 62% of these isolates were resistant to fusidic acid (FA). During the inclusion period, FA resistance rate was similar (60%). Genetic characterization evidenced CC6 as the predominant clonal complex (70%) with 26 isolates (53%) identified as CC6-MRSA-[IV+ fus ] (PVL+). Conclusions: These findings demonstrated a low diversity of MRSA in New Caledonia, with the dominance of a clonal complex not reported previously. The frequent fusidic acid (FA) resistance in MRSA was associated with a high prevalence of fusC gene, suggesting that FA misuse contributed to driving the selection of this clone. Our findings suggest the recommendation to stop the topical use of FA to control the emergence of this severe MRSA clone and decrease the rate of MRSA in New Caledonia.